Sirr dan Jahr dalam Bacaan Sholat Perspektif Ma’anil Hadits - Rian Rahmat Hidayat; Ghozali, Abdul Malik; Bastari, Ahmad (AN NUR: Jurnal Studi Islam, 2024)
With the books of hadith and syarah as the primary sources, this essay seeks to investigate scholarly perspectives on the recitation of sirr and jahr in prayer as well as relevant hadiths. This study compares scholarly perspectives about the interpretation of sirr and jahr and conducts a thorough hadith analysis using the book of Syarah. This research used a qualitative methodology with an emphasis on content analysis using data from the literature. The study's conclusions demonstrate that the relevant hadiths provide a thorough justification for the recital of sirr and jahr during prayer. Yearning to enhance spiritual appreciation and benefit the makmum who hears it, jahr is said throughout the Maghrib, Isha, and Fajr prayers. Conversely, the recital of sirr, as in the prayers of Dhuhur and Asr, seeks to preserve individual solemnity and prevent disruption of the surrounding environment. This research highlights how crucial it is to have a thorough comprehension of the wisdom behind each instruction while putting the teachings of the Prophet Muhammad SAW into practice via prayer.